The E-selectin S149R polymorphisms in breast cancer in a northern Iran population - Golnarnik, G; Mashayekhi, F; Saedi, H S (Cellular and Molecular Biology, 2016)
Breast cancer is a complex polygenic disorder that genetic factors play an important role in disease etiology. E-selectin mediates the adhesion of tumor cells to endothelial cells. This interaction is associated with metastatic dissemination. Expression of E-selectin on the endothelium is a hallmark of inflammation. This study was performed to evaluate the association of E-selectin S149R polymorphisms and the risk of breast cancer. A total of 100 patients with breast cancer and 120 healthy sample donors (controls) were recruited in this study. Genomic DNA was extracted from fresh blood samples and genotyping of the E-selectin genes was performed using PCR-restriction fragment length polymorphism (PCR-RFLP). The frequencies of the CC, AC and AA genotypes were 2%, 84%, and 14% in patients and 2%, 12%, and 86 % in controls, respectively, while the A and C allelic frequency was 56%, 44% in patients and 92%, 8% in controls, respectively. Statistical analysis showed that there is a significant difference between two groups (P<0.0001). It is concluded that the E-selectin S149R polymorphisms is associated with the oncogenesis of breast cancer in a population in northern Iran.